1993
DOI: 10.1159/000177760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Phytosterols on Liver Lipids and Lipid Metabolism Enzymes

Abstract: The effects of dietary phytosterols on lipid metabolism have been assessed through determination of liver lipids (sterols and fatty acids) and lipid metabolism enzymes (acetyl-CoA carboxylase, malic enzyme, glucose-6-phosphate dehydrogenase) in rats fed 12 or 24 mg cholesterol a day and 0-96 mg phytosterols. The results indicate that, provided the dietary phytosterol to cholesterol ratio is at least 1 and in the presence of a dietary cholesterol excess, phytosterols do exert a regulatory role through decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 13 publications
0
15
1
1
Order By: Relevance
“…After deamination, the carbon residues from amino acids may contribute to the acetyl‐CoA pool and therefore play a significant metabolic role as a primary substrate for lipogenesis or gluconeogenesis (Moon & Mommsen 1987). The mechanisms mediating the dietary protein quality modulation of de novo fatty acid synthesis are ill‐defined, but the differences in the amino acid composition of the proteins and the levels of certain antinutritional factors have been cited as major factors (Herzberg 1991; Laraki, Pelletier, Mourot & Debry 1993). Experiments with rainbow trout and European seabass have shown that G6PD and ME activities were depressed by SPC‐rich diets (Dias 1999).…”
Section: Discussionmentioning
confidence: 99%
“…After deamination, the carbon residues from amino acids may contribute to the acetyl‐CoA pool and therefore play a significant metabolic role as a primary substrate for lipogenesis or gluconeogenesis (Moon & Mommsen 1987). The mechanisms mediating the dietary protein quality modulation of de novo fatty acid synthesis are ill‐defined, but the differences in the amino acid composition of the proteins and the levels of certain antinutritional factors have been cited as major factors (Herzberg 1991; Laraki, Pelletier, Mourot & Debry 1993). Experiments with rainbow trout and European seabass have shown that G6PD and ME activities were depressed by SPC‐rich diets (Dias 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Plant sterols fed to rats have been reported to reduce plasma total, LDL and VLDL cholesterol and triglyceride and liver cholesterol concentrations and to increase markedly (up four to nine times) liver campesterol and sitosterol contents 235. 236 In hamsters, sitostanol feeding lowered serum and hepatic cholesterol but increased serum campesterol concentration in low‐sitostanol or tallow oil sterol groups, while the hepatic sitosterol level was increased by feeding a synthetic sitostanol mixture 237. In rats, sitostanol feeding in the form of tallow oil sterols lowered LDL cholesterol but increased HDL cholesterol proportionately to LDL cholesterol.…”
Section: Bioavailability and Physiological Effectsmentioning
confidence: 99%
“…Furthermore, chemical analysis has also revealed that MC has many phytochemicals which may delay gastric transient time, and function to prevented damage to key tissues (pancreas, liver) involved in the regulation of glucose metabolism (Krochmal et al, 2004;Kumar Shetty et al, 2005;Laraki et al, 1993;Lau et al, 1998;Matsuda et al, 1999a,b;Murakami et al, 2001;Parkash et al, 2002;Sathishsekar and Subramanian, 2005;Wang and Ng, 1998).…”
Section: Introductionmentioning
confidence: 99%